To evaluate alteration of salivary sodium and potassium level in hypertensive patients with and without medication - JK Mitra; Vinayak Kumar Mantu; Ruchi Mitra (International Journal of Medical Research and Review, 2015)
Aim: to study the alterations of sodium and potassium in saliva with change in blood pressure values and to estimate sodium and potassium level in saliva in controls and hypertensive’s with the comparison and correlation of their changes.Materials and methods: 58 patients of age group between 30-70 years with 43 hypertensives and 15 controls were examined in medicine department Rajendra Institute of Medical Sciences, Ranchi for a period of about 5 weeks(one month) and unstimulated saliva was collected before and after treatment with antihypertensive drugs.Results: The hypertensive patients were characterized with significantly elevated levels of potassium ion(p=0.000) and less remarkable increase of sodium ion (p=0.24) after one month treatment as compared to controls. Also the salivary potassium ion was more marked in patients under Atenolol antihypertensive drug.Conclusions: The result may be related to the hypothesis of chronic adrenergic over stimulation of the salivary glands in hypertensive patients. Salivary concentrations of sodium and potassium ion can be used as a valuable marker and diagnostic aid in hypertensive patients.